Effects of variations in atmospheric temperature and humidity on the estimation of exclusive breastfeeding status using the deuterium oxide dose-to-mother technique - Baby, Jeswin; Kaestel, Pernille; Preston, Tom; Duffull, Stephen B.; Liu, Zheng; Diana, Aly; Houghton, Lisa; Kurpad, Anura V.; Thomas, Tinku (Frontiers in Pediatrics, 2023)
The deuterium dose-to-mother (DTM) method measures the breast milk intake of breastfed children. Recently, the use of this method has been expanded to classify babies objectively as exclusively breast fed (EBF) or not (non-EBF) based on quantification of nonmilk oral water intake (NMOI). However, the validity of NMOI estimates depends on the atmospheric temperature and humidity. Objective: To evaluate the effects of atmospheric temperature and humidity on NMOI calculation and the classification of exclusive breastfeeding. Methods: The effect of indoor temperature and relative humidity on NMOI and the estimated prevalence of non-EBF were examined in two existing data sets of DTM in children by varying temperature in the range of 15 to 35°C and relative humidity in the range of 20% to 80% representing the maximum span of indoor conditions expected. Populationlevel estimates of NMOI distributions were derived using the rstan package for R v2.21.2.The NMOI decreased at a rate of -1.15 g/day per °C increase and at a rate of -1.01 g/day per percent increase in relative humidity; this was due to variations in non-oral water intake from the atmosphere, a component of the calculation of NMOI, which is dependent on temperature and humidity. For the various locations considered, the mean calculated NMOI varied between 24.6 and 53.3 g/day. In the mixed-fed sample of babies, the prevalence of non-EBF based on the earlier defined NMOI cut-off of 86.6 g/day was reduced by 19% when relative humidity was increased by 60%. Conclusions: Atmospheric conditions are essential factors in the computation of NMOI, used in the objective classification of babies as exclusively breast fed or not, and should be considered when the DTM method is used to classify exclusive breastfeeding.